ANALISIS PRINSIP KESOPANAN DALAM INTERAKSI BERBAHASA ANAK ASRAMA PUTRI ROSA MISTIKA DESA PENFUI TIMUR - Marie Elisabeth Ndejeng; Simon Sabon Ola; Anastasia Janery Manga Leda (Jurnal Lazuardi, 2026)
This study aims to examine or determine the number of errors or deviations in language politeness in humans when communicating with others. This research focused on children at the Rosa Mistika Girls' Dormitory in East Penfui Village because in everyday life, there are various forms of speech that are interesting to study, such as how they give advice, reprimand friends, ask for help, and respond to conversations while maintaining politeness. The research method used was qualitative. Data collection techniques included observation, photography, audio recording, and the free listening technique. Data analysis included data tabulation, data presentation, and drawing conclusions. The results showed the application of maxim indicators frequently used by the boarding school children, namely the maxim of wisdom/tact, the maxim of generosity, the maxim of praise/appreciation, the maxim of humility, the maxim of agreement/appropriation, and the maxim of sympathy.